Response of Classic Spar by Morison Equation and Diffraction Theory - Kurian, V.J. (2010)
ABSTRACT This paper presents the numerical hydrodynamic analysis and comparison of the motion responses of offshore spar platforms in regular sea waves using Morison equation and diffraction method. The classic spar was modeled as a rigid body with three degrees of freedom restrained by mooring lines. Linear Airy wave theory and Morison equation were used for calculating the wave forces on the structure in the first case. The mass, damping and stiffness matrices were evaluated at every time step and the equations of motion were formulated for the platform dynamic equilibrium. The equations were solved using Newmark Beta time domain dynamic analysis method. The results were obtained as transfer functions in surge, heave and pitch. In the second case, the transfer functions were obtained using software based on linear diffraction method. The calculation of wave forces using Morison equation was found to give significant errors, especially in the low frequency range. KEYWORDS Spar platforms, Hydrodynamic analysis, Degree of Freedom (DOF), Morison modified equations, Diffraction Method, Transfer Function.